Collectifs et développement durable des territoires ruraux en Amérique latine - Céline Raimbert; Nasser Rebaï (EchoGéo)
For several decades, the Latin American countryside has been experiencing significant changes under the influence of policies that promote a capitalist model of rural development. However, we observe at the same time a growing mobilization of peasant groups who claim a change of economic paradigm and a better recognition of family farming. In this context, this article proposes a thought on the role of the collectives for the sustainable development of rural Latin American territories based on several case studies in Brazil and Ecuador.